\(\sqrt{16-8\sqrt{3}}-\sqrt{16+8\sqrt{3}}\)

Rút gọn biểu thức trên

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

17 tháng 7 2021

\(\sqrt{16-8\sqrt{3}}-\sqrt{16+8\sqrt{3}}=\sqrt{12-8\sqrt{3}+4}-\sqrt{12+8\sqrt{3}+4}\)

\(=\sqrt{\left(2\sqrt{3}-2\right)^2-\sqrt{\left(2\sqrt{3}+2\right)^2}}=2\sqrt{3}-2-2\sqrt{3}-2=-4\)

18 tháng 6 2019

a, \(\sqrt{3-\sqrt{5}}+\sqrt{7-3\sqrt{5}}\)\(=\sqrt{\frac{1}{2}.\left(6-2\sqrt{5}\right)}\)\(+\sqrt{\frac{1}{2}.\left(14-2.3\sqrt{5}\right)}\)

\(=\sqrt{\frac{1}{2}.\left(\sqrt{5}-1\right)^2}\)\(+\sqrt{\frac{1}{2}.\left(3-\sqrt{5}\right)^2}\)\(=\frac{\sqrt{2}}{2}.\left(\sqrt{5}-1\right)+\frac{\sqrt{2}}{2}.\left(3-\sqrt{5}\right)\)

\(=\frac{\sqrt{2}}{2}.2=\sqrt{2}\)

Câu b đề đúng ko bn

30 tháng 8 2018

a) \(\frac{\sqrt{6}+\sqrt{14}}{2\sqrt{3}+\sqrt{28}}=\frac{\sqrt{2}\left(\sqrt{3}+\sqrt{7}\right)}{2\left(\sqrt{3}+\sqrt{7}\right)}=\frac{1}{\sqrt{2}}\)

b) \(\frac{\sqrt{2}+\sqrt{3}+\sqrt{6}+\sqrt{8}+\sqrt{16}}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=\frac{\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)+\left(\sqrt{4}+\sqrt{6}+\sqrt{8}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=\frac{\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)\left(1+\sqrt{2}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=1+\sqrt{2}\)

6 tháng 7 2019

\(b,\frac{2+\sqrt{3}}{1-\sqrt{4-2\sqrt{3}}}+\frac{2-\sqrt{3}}{1+\sqrt{4+2\sqrt{3}}}\)

\(=\frac{2+\sqrt{3}}{1-\sqrt{3-2\sqrt{3}+1}}+\frac{2-\sqrt{3}}{1+\sqrt{3+2\sqrt{3}+1}}\)

\(=\frac{2+\sqrt{3}}{1-\sqrt{\left(\sqrt{3}-1\right)^2}}+\frac{2-\sqrt{3}}{1+\sqrt{\left(\sqrt{3}+1\right)^2}}\)

\(=\frac{2+\sqrt{3}}{1-\left(\sqrt{3}-1\right)}+\frac{2-\sqrt{3}}{1+\sqrt{3}+1}\)

\(=\frac{2+\sqrt{3}}{2-\sqrt{3}}+\frac{2-\sqrt{3}}{2+\sqrt{3}}\)

\(=\frac{\left(2+\sqrt{3}\right)^2}{\left(2-\sqrt{3}\right)\left(2+\sqrt{3}\right)}+\frac{\left(2-\sqrt{3}\right)^2}{\left(2-\sqrt{3}\right)\left(2+\sqrt{3}\right)}\)

\(=\frac{4+4\sqrt{3}+3+4-4\sqrt{3}+3}{4-3}\)

\(=14\)

6 tháng 7 2019

\(a,\frac{\sqrt{2}+\sqrt{3}+\sqrt{6}+\sqrt{8}+\sqrt{16}}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=\frac{\sqrt{2}+\sqrt{3}+4+\sqrt{6}+\sqrt{8}}{\sqrt{2}+\sqrt{3}+2}\)

\(=\frac{\sqrt{2}+\sqrt{3}+2}{\sqrt{2}+\sqrt{3}+2}+\frac{\sqrt{2}.\sqrt{2}+\sqrt{2}.\sqrt{3}+\sqrt{2}.2}{\sqrt{2}+\sqrt{3}+2}\)

\(=1+\frac{\sqrt{2}\left(\sqrt{2}+\sqrt{3}+2\right)}{\sqrt{2}+\sqrt{3}+2}\)

\(=1+\sqrt{2}\)

13 tháng 7 2017

\(\dfrac{\sqrt{2}+\sqrt{3}+\sqrt{6}+\sqrt{8}+\sqrt{16}}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=\dfrac{\sqrt{2}+\sqrt{3}+\sqrt{6}+\sqrt{8}+\sqrt{4}+\sqrt{4}}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=\dfrac{\sqrt{2}+\sqrt{3}+\sqrt{4}+\sqrt{4}+\sqrt{6}+\sqrt{8}}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=\dfrac{\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)+\sqrt{2}\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=\dfrac{\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)\left(1+\sqrt{2}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=1+\sqrt{2}\)

AH
Akai Haruma
Giáo viên
17 tháng 6 2019

Lời giải:
a)

\(\sqrt{3-\sqrt{5}}+\sqrt{7-3\sqrt{5}}=\sqrt{\frac{6-2\sqrt{5}}{2}}+\sqrt{\frac{14-6\sqrt{5}}{2}}\)

\(=\sqrt{\frac{5+1-2\sqrt{5.1}}{2}}+\sqrt{\frac{3^2+5-2.3\sqrt{5}}{2}}\)

\(=\sqrt{\frac{(\sqrt{5}-1)^2}{2}}+\sqrt{\frac{(3-\sqrt{5})^2}{2}}\)

\(=\frac{\sqrt{5}-1}{\sqrt{2}}+\frac{3-\sqrt{5}}{\sqrt{2}}=\frac{2}{\sqrt{2}}=\sqrt{2}\)

b)

\(\sqrt{8-2\sqrt{7}}-\sqrt{16+5\sqrt{7}}=\sqrt{7+1-2\sqrt{7.1}}-\sqrt{\frac{32+10\sqrt{7}}{2}}\)

\(=\sqrt{(\sqrt{7}-1)^2}-\sqrt{\frac{5^2+7+2.5\sqrt{7}}{2}}\)

\(=\sqrt{(\sqrt{7}-1)^2}-\sqrt{\frac{(5+\sqrt{7})^2}{2}}=\sqrt{7}-1-\frac{5+\sqrt{7}}{\sqrt{2}}\)

\(=\frac{\sqrt{14}-\sqrt{2}-5-\sqrt{7}}{\sqrt{2}}\)

AH
Akai Haruma
Giáo viên
1 tháng 5 2019

Lời giải:
a)

\(\sqrt{3-\sqrt{5}}+\sqrt{7-3\sqrt{5}}=\sqrt{\frac{6-2\sqrt{5}}{2}}+\sqrt{\frac{14-6\sqrt{5}}{2}}\)

\(=\sqrt{\frac{5+1-2\sqrt{5.1}}{2}}+\sqrt{\frac{3^2+5-2.3\sqrt{5}}{2}}\)

\(=\sqrt{\frac{(\sqrt{5}-1)^2}{2}}+\sqrt{\frac{(3-\sqrt{5})^2}{2}}\)

\(=\frac{\sqrt{5}-1}{\sqrt{2}}+\frac{3-\sqrt{5}}{\sqrt{2}}=\frac{2}{\sqrt{2}}=\sqrt{2}\)

b)

\(\sqrt{8-2\sqrt{7}}-\sqrt{16+5\sqrt{7}}=\sqrt{7+1-2\sqrt{7.1}}-\sqrt{\frac{32+10\sqrt{7}}{2}}\)

\(=\sqrt{(\sqrt{7}-1)^2}-\sqrt{\frac{5^2+7+2.5\sqrt{7}}{2}}\)

\(=\sqrt{(\sqrt{7}-1)^2}-\sqrt{\frac{(5+\sqrt{7})^2}{2}}=\sqrt{7}-1-\frac{5+\sqrt{7}}{\sqrt{2}}\)

\(=\frac{\sqrt{14}-\sqrt{2}-5-\sqrt{7}}{\sqrt{2}}\)

9 tháng 9 2019

a) P= \(\sqrt{a+1-2\sqrt{a}}-\sqrt{a+16-8\sqrt{a}}\)

 =\(\sqrt{\left(\sqrt{a}-1\right)^2}-\sqrt{\left(\sqrt{a}-4\right)^2}\)

 =\(|\sqrt{a}-1|-|\sqrt{a}-4|\)

 TH1: P= 1 - \(\sqrt{a}\)- 4 + \(\sqrt{a}\)=-3 khi \(0\le a\le1\)

TH2: P= \(\sqrt{a}\)-1 -4+\(\sqrt{a}\)=-5 + \(2\sqrt{a}\) khi \(1\le a\le4\)

TH3 : P=\(\sqrt{a}\)-1 -\(\sqrt{a}\)+4 =3 khi \(a\ge4\)

Vậy ...

13 tháng 8 2016

a) \(\frac{\sqrt{6}+\sqrt{14}}{2\sqrt{3}+\sqrt{28}}=\frac{\sqrt{6}+\sqrt{14}}{\sqrt{2}\left(\sqrt{6}+\sqrt{14}\right)}=\frac{1}{\sqrt{2}}=\frac{\sqrt{2}}{2}\)

b) \(\frac{\sqrt{2}+\sqrt{3}+\sqrt{6}+\sqrt{8}+\sqrt{16}}{\sqrt{2}+\sqrt{3}+\sqrt{4}}=\frac{\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)+\sqrt{2}\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(\frac{\left(\sqrt{2}+1\right)\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}=\sqrt{2}+1\)

 

13 tháng 8 2016

\(\frac{\sqrt{2}+\sqrt{3}+\sqrt{6}+\sqrt{8}+\sqrt{16}}{\sqrt{2}+\sqrt{3}+\sqrt{4}}=\frac{\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)+\left(\sqrt{4}+\sqrt{6}+\sqrt{8}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}\)

\(=\frac{\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)+\sqrt{2}\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}=\frac{\left(1+\sqrt{2}\right)\left(\sqrt{2}+\sqrt{3}+\sqrt{4}\right)}{\sqrt{2}+\sqrt{3}+\sqrt{4}}=1+\sqrt{2}\)